Risk factors for covered metallic stent migration in patients with distal malignant biliary obstruction due to pancreatic cancer. Issue 9 (September 2014) - Nakai, Yousuke; Isayama, Hiroyuki; Kogure, Hirofumi; Hamada, Tsuyoshi; Togawa, Osamu; Ito, Yukiko; Matsubara, Saburo; Arizumi, Toshihiko; Yagioka, Hiroshi; Mizuno, Suguru; Sasaki, Takashi; Yamamoto, Natsuyo; et al.
Abstract Background and Aim Covered metallic stents (CMSs) were developed to overcome tumor ingrowth in uncovered metallic stents (UMSs) for malignant biliary obstruction, but superiority of CMSs over UMSs is still controversial due to the high migration rate in CMS. Therefore, we conducted this retrospective analysis to clarify risk factors for stent migration, including mechanical properties of CMSs. Methods Patients with unresectable pancreatic cancer, receiving CMS for distal malignant biliary obstruction in five tertiary care centers, were retrospectively studied. Univariate and multivariate analyses to identify prognostic factors for early (< 6 months) stent migration were performed using a proportional hazards model with death or stent occlusion without stent migration as a competing risk. Two mechanical properties were included in the analysis: axial force, the recovery force that leads to a CMS straightening, and radial force (RF), the expansion force against the stricture. Results Among 290 patients who received CMS placement for distal malignant biliary obstruction, stent migration rate was 15.2%. CMS migrated early (< 6 months) in 10.0% and distally in 11.7%, respectively. In the multivariate analysis, significant risk factors for early stent migration were chemotherapy (subdistribution hazard ratios [SHR] 4.46, P = 0.01), CMS with low RF (SHR 2.23, P = 0.03), and duodenal invasion (SHR 2.25, P = 0.02). Conclusion CMS with low RF, chemotherapy, and duodenal invasion were associated with CMS migration from our study.